MIR143 Inhibits Steroidogenesis and Induces Apoptosis Repressed by H3K27me3 in Granulosa Cells - Zhong, Yuyi; Li, Liying; Chen, Zitao; Diao, Shuqi; He, Yingting; Zhang, Zhe; Zhang, Hao; Yuan, Xiaolong; Li, Jiaqi (Frontiers in Cell and Developmental Biology, 2020)
The granulosa cell growth factor and apoptotic factor are two factors to determine follicular apoptosis. Whether ssc-miR-143-3p (MIR143) plays as an apoptosis factor in porcine granulosa cells (pGCs) remain unclear. This study tries to investigate what function of MIR143 is and how MIR143 gets these functions in pGCs from 3-5 mm medium-sized follicles. Firstly, 5'RACE was used to identify the structure of MIR143, and in-situ hybridization, qPCR, and DNA pull-down were employed to exhibit the spatio-temporal expression and transcriptional regulation of MIR143. Furthermore, ELISA, Western blotting, and flow cytometry were adopted to explore the functions of MIR143 in pGCs. It was found that MIR143 was an exonic miRNA located in host gene LOC100514340 with an increasing expression during follicular growth. Moreover, MIR143 suppressed steroidogenesis related genes of HSD17β4, ER1, and PTGS2, negatively regulating estrogen, androgen, progesterone, and prostaglandin. MIR143 induced the apoptosis via activation of BAX-dependent Caspase 3 signaling. Furthermore, H3K27me3 influenced the recruitment of transcription factors and binding proteins to repress MIR143 transcription. At last, H3K27me3 agonist with MIR143 inhibition activated steroidogenesis but repressed apoptosis. These findings suggest that H3K27me3-mediated MIR143 inhibition play a critical role in follicular atresia by regulating cell apoptosis and steroidogenesis, which will provide useful information for further investigations of H3K27me3-miediated MIR143 epigenetic regulation in follicular growth in mammals.